Students’ Dependence on AI in English Learning: A Qualitative Study on Its Impact on Critical Thinking - Abdillah Ikhsan Faqih; Ridwan Ridwan (Alinea: Jurnal Bahasa, Sastra dan Pengajaran, 2026)
This study aims to investigate in depth how students' reliance on AI in English learning shapes, limits, or transforms their critical thinking processes in the context of English as a Foreign Language (EFL) in vocational secondary education. This study used a qualitative approach with a case study design to examine students' reliance on AI and its implications for critical thinking skills in English as a Foreign Language (EFL) learning. The study was conducted at SMKN 1 Bangorejo Banyuwangi, which was purposively selected because it has utilized AI applications in English learning. The research subjects were determined through purposive sampling, namely students who actively use AI. Data collection was conducted through in-depth interviews, learning observations, and document analysis. Data were analyzed thematically through the stages of reduction, presentation, and drawing conclusions. The results of this study indicate that the use of artificial intelligence (AI) in English learning at SMKN 1 Bangorejo has a dual impact on student learning. On the one hand, AI has been shown to improve the linguistic quality of students' writing, particularly in aspects of grammar, sentence structure, and vocabulary. However, this improvement was not accompanied by a balanced development of critical thinking. Intensive use of AI tends to shift students' learning orientation from cognitive processes to end results, limiting analysis, evaluation, and reflection. This situation has the potential to trigger cognitive dependency or cognitive offloading. This finding emphasizes the importance of teachers' role in designing pedagogical strategies that position AI as a supporting tool, not a substitute for thinking processes, to maintain a balance between linguistic achievement and cognitive depth.